2010
DOI: 10.1109/tps.2010.2056393
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Plasma Inducing Cell Apoptosis

Abstract: A cold atmospheric-pressure plasma, which has been widely used for biomedical applications, may potentially affect the cell cycle and cause cell apoptosis. In this paper, a human hepatocellular carcinoma cell (HepG2) is treated by a singleelectrode plasma jet device. Further investigation by using flow cytometric analysis demonstrates that plasma treatment increases the percentage of apoptotic cells being associated with cell cycle arrest at the G2/M phase. Moreover, the reverse transcription polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…They found the expression of the p21 CDK inhibitor (cell cycle inhibitor) and the protein p53 are increased [149]. …”
Section: Methods Of Productionmentioning
confidence: 99%
“…They found the expression of the p21 CDK inhibitor (cell cycle inhibitor) and the protein p53 are increased [149]. …”
Section: Methods Of Productionmentioning
confidence: 99%
“…Investigators reported that the effects of LTP on biological cells (prokaryotes and eukaryotes) are mediated by reactive oxygen and nitrogen species (RONS) [11,12,[59][60][61][62][63][64][65][66]. These species include hydroxyl, OH, atomic oxygen, O, singlet delta oxygen, O 2 ( 1 ∆), superoxide, O 2 − , hydrogen peroxide, H 2 O 2 , and nitric oxide, NO.…”
Section: Mechanisms Of Biological Action Of Ltp: Brief Summarymentioning
confidence: 99%
“…When irradiated to water, it generates a variety of chemical species, including reactive oxygen species (ROS) with only a slight change in temperature [11]. Application of atmospheric plasma flow to cells has been studied due to this feature, and various effects have been observed to date: induction of apoptosis [12,13], cell cycle arrest [14], reduction of tumor size [15], and selective death of melanoma cells [16].…”
Section: Introductionmentioning
confidence: 99%